History of Police Reforms in Kenya, 1885 - 2022 - Masake, Elon (JOOUST, 2023)
The study analyzed the police reforms implemented in Kenya starting from 1885. The inaugural police station in Kenya was founded in Mombasa in 1896, merely a year subsequent to the proclamation of the Protectorate. Subsequently, in 1920, a contemporary police force was established with the primary objective of ensuring security. Consequently, the police were predominantly employed as a "punitive citizen containment squad." Throughout the independence and post-independence period era, reforms were made to enhance the organization and efficacy of the Kenyan police force. Nevertheless, despite certain measures being undertaken, there is still a pressing need for substantial reforms, and the legislation controlling police reform has yet to be enforced. The absence of advancement in implementing the reform agenda elevates the potential for infringements on human rights and hampers the police's capacity to address such infringements in an equitable and efficient manner. The study's primary objective was to investigate the history of police reforms in Kenya from 1885 to 2022. The specific objectives were to examine the transformation of the Police Force in Kenya during the colonial period (1885-1963), assess the nature and scope of Police Reforms in Kenya since 1964, analyse the implementation of police reforms in Kenya (2007-2022) and assess the progress and challenges on implementation of the police reform package and emergent possible solutions. The study employed Kurt Lewin's three-step transition theory, also known as the theory of change to analyze and present the findings. A historical research design was employed, utilizing semi structured interview guides and conducting in-depth interviews with key informants. The study targeted a population of 210 police officers in 7 Sub- County police stations and 17 key informants drawn from the civil society and the public. In each station, the police officers/constables were sampled purposively based on years of experience and responsibilities. Similarly, Key informants who included station commanders and civil society members were purposively sampled. The sample size for police officers and key informants were 21 and 17 respectively. A semi-structured interview schedule was used to conduct interviews with the Officers Commanding Stations and members of civil society because of its flexibility to gather in-depth information from sensitive topics. On the other hand, open ended questionnaires were used to collect data from police officers from all the police stations because of its ability to collect information from large samples and uphold confidentiality. Secondary data was gathered by conducting a thematic assessment of literature pertaining to police reforms. Qualitative data was analyzed using thematic method. The study revealed a significant lack of awareness among police officers regarding police reforms. The report also indicated that the enforcement of a new hierarchical system and the thorough examination of police officers had encountered challenges in adhering to legal requirements. The study recommended that the National Police Service Commission should initiate a comprehensive evaluation of all police officers and conduct informative campaigns to educate them about the significance of police reforms. Additional areas for further research should assess the manner in which police officers have embraced the new organizations such as the National Police Service Commission, the Independent Police Oversight Authority, and the office of the Inspector General. Further research on police reforms in Kenya should also be done within the larger context of security sector reforms in order to harmonize and integrate security concerns in Kenya.
Keywords: Police Reforms